Analisis Pengaruh ISO Kamera dan Shutter Speed terhadap Penyimpangan Dimensi pada Fotogrametri dalam Reverse Engineering - Muhammad Jauhari Fikkri; Wirawan Wirawan (International Forum of Researchers and Lecturers, 2025)
Photogrammetry is an important technique in the reverse engineering process to reconstruct 3D images without requiring initial design data. This technique allows the creation of digital models of physical objects through processing a series of two-dimensional images. This study aims to analyze the effect of camera ISO settings and shutter speed on the level of dimensional deviation in the reconstructed 3D model. The method used is an experiment with a quantitative approach, involving a series of software for the 3D image reconstruction process, mesh structure preparation, and digital dimension measurement. The ISO variations used in the image capture were 250, 400, 500, and 800, while the shutter speed variations applied included 1/125 second, 1/100 second, 1/50 second, and 1/25 second. The test object was a cylinder with an actual diameter of 50 mm. The obtained 3D model results were compared with the actual dimensions through a Two-Way ANOVA statistical analysis to test the significance of the influence of both variables. The results showed that both ISO and shutter speed had a significant effect on the dimensional deviation of the 3D model. The combination of camera settings with ISO 500 and shutter speed 1/125 second produced the smallest deviation, while the combination of ISO 800 and shutter speed 1/25 second gave the largest deviation. The coefficient of determination (R²) value of 99.02% indicates that the statistical model used is very strong in explaining the variation of deviation. This research contributes to the optimal setting of camera parameters to improve the accuracy of photogrammetry results in reverse engineering applications.